ANALISIS PENGELUARAN KONSUMSI RUMAH TANGGA NELAYAN DI PANTAI SENDANG BIRU KABUPATEN MALANG, JAWA TIMUR - do, Suman (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine fisherman household consumption expenditure in Sendang Biru Beach Malang Distric, East Java, which is influenced by several factors. This research was conducted by stratified random sampling method. The data used in this study was obtained from observation and questionnaires on fisherman household consumption expenditure in Sendang Biru Beach in the period from June to September. Method of data analysis is using multiple linear regression analysis to determine the effect of Revenue, Number of Family Members, Children's Education, Employment Type, Age, and Health to the Fishernman Household Consumption Expenditure in Sendang Biru Beach in Malang District, East Java. Based normality test, multicollinearity, and heteroscedasticity test did not reveal any deviation from the classical assumptions. The results showed that simultaneous discussion that variable income, number of family members, children's education, employment class, age, and health have a significant effect on fisherman household consumption expenditure. The partialâ€™s result showed that the variable income, number of family members, children's education, class work, and age, have the significant effect and positve. Whereas no significant effect on the health on fisherman household consumption expenditures. R-square value is 69.7% , indicates that consumption expenditure can be explained by the study variables is 69.7%.Keywords: consumption expenditures, income, education of children, fishermen, sendang biruÂ